Self-Efficacy, Work Environment, and Discipline Shaping Employee Job Satisfaction: Keyakinan Diri, Lingkungan Kerja, dan Disiplin dalam Mempengaruhi Kepuasan Kerja Karyawan - Rahmatullah, Alif Maulana; Firdaus, Vera (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Job satisfaction is a central component of organizational success, influencing employee performance and company sustainability. Specific Background: Within the context of PT. Sinaraya Nugraha Ahmadaris Medika, low employee satisfaction was observed, associated with insufficient confidence, suboptimal work environment, and weak discipline practices. Knowledge Gap: Previous studies have not comprehensively examined the interrelationship between self-efficacy, work environment, and work discipline within the healthcare industry in Indonesia. Aims: This study aims to analyze the relationship between self-efficacy, work environment, and work discipline toward job satisfaction among employees. Results: Using multiple linear regression on 117 respondents, findings reveal that self-efficacy, work environment, and work discipline each show a positive and significant association with job satisfaction, both partially and simultaneously. Novelty: This research integrates psychological and environmental dimensions in explaining job satisfaction within the medical equipment sector, an area rarely addressed in previous studies. Implications: The results provide empirical insights for human resource strategies that emphasize confidence-building, conducive work settings, and strong discipline systems to enhance employee satisfaction and performance. Highlights: Self-efficacy, environment, and discipline jointly enhance job satisfaction. Novel integration of psychological and workplace factors in HR studies. Empirical evidence from Indonesia’s medical equipment industry context. Keywords: Self-efficacy; Work Environment; Work Discipline; Job Satisfaction; Human Resource Management